Early rehabilitation after orthotopic heart transplantation: a case study - Natalya V. Fedorova; Yulia A. Argunova; Ekaterina N. Prilutskaya; Olga L. Barbarash (КардиоСоматика)
BACKGROUND: Publications on rehabilitation in patients following heart transplantation remain limited. This issue is currently being actively investigated, as there is a lack of clear data on the optimal timing for initiating physical rehabilitation, the use of exercise testing for objective assessment of patient condition, or the types of physical training.